Application of chromatography-mass spectrometry to determine free and esterified fatty acids in their combined presence in plant raw materials - M. N. Lyutikova; Yu. P. Turov; E. H. Botirov (Тонкие химические технологии, 2013)
In comparison with other types of matter, plants have a small content of fatty acids (FA). They perform energetic, structural and protective functions. Lipids actively change metabolism in the autumn time and increase the resistance of plants to low temperatures. For this reason the study of plant lipids is important to determine the chemical composition of lipids and understand of their role in the metabolism of plants. Analysis of the lipid composition of plant is connected with some complications. Plants can contain fatty acids not only in the free form, but also in the form of their esters. This can lead to errors in the quantitative determination of FA in plant samples. In addition, the presence of a significant variety of chemical compounds in plants complicates the analysis. The article describes the results of a study on fatty acids and their esters in cowberries and cranberries by gas chromatography-mass spectrometry. It is shown that during the fractionating of berry extracts, fatty acids are in the chloroform extract of the acids, and their esters are in the hexane fraction. Thus, we can obtain the chromatogram of extracts with a clear picture of the peaks of identified compounds (Rs > 1.5). The linear dependence remains in the range of identified compounds 0.01–300 mg/mL. Evaluation of the metrological characteristics of the analysis techniques was performed with a pattern mixture of methyl esters of fatty acids as an example.